2004
DOI: 10.1097/01.cad.0000131681.21637.b2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical development of new mitotic inhibitors that stabilize the microtubule

Abstract: Microtubule-stabilizing agents are increasingly studied for cancer treatment based largely on the prior success of paclitaxel and docetaxel. In this review, we focus on the clinical development of epothilones and discodermolide, and we discuss salient preclinical and clinical highlights of these two novel natural products. These agents are distinguished by their biochemical features making them poor P-glycoprotein substrates and capable of inducing cytotoxicity in cell lines or in vivo tumor models harboring m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…16 The discovery of numerous compounds from natural sources which display a wide structural diversity and are cytotoxic by perturbation of the dynamic instability of microtubules has attracted much attention within the last two decades. [17][18][19][20] Microtubules have, therefore, become an attractive pharmacological target for anticancer drug discovery. [17][18][19][20] Almost all antimitotic agents interact with the α/β-tubulin dimer, rather than microtubule-associated proteins (MAPs) or other proteins involved in microtubule functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The discovery of numerous compounds from natural sources which display a wide structural diversity and are cytotoxic by perturbation of the dynamic instability of microtubules has attracted much attention within the last two decades. [17][18][19][20] Microtubules have, therefore, become an attractive pharmacological target for anticancer drug discovery. [17][18][19][20] Almost all antimitotic agents interact with the α/β-tubulin dimer, rather than microtubule-associated proteins (MAPs) or other proteins involved in microtubule functions.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Microtubules have, therefore, become an attractive pharmacological target for anticancer drug discovery. [17][18][19][20] Almost all antimitotic agents interact with the α/β-tubulin dimer, rather than microtubule-associated proteins (MAPs) or other proteins involved in microtubule functions. The Vinca alkaloids, exemplified by vinblastine (Chart 1) and vincristine (Chart 1), as well as the taxanes, such as paclitaxel (Chart 1) and the semisynthetic analogue docetaxel (Chart 1), are the most commonly used antimitotic agents in the clinical treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…41 Two epothilones, ixabepilone and patupilone, in clinical studies, have shown significant activity in men with CRPC. [42][43][44][45] A phase II study conducted by the Southwest Oncology Group (SWOG) included 42 men with chemotherapy-naive CRPC who received ixabepilone (40 mg/m 2 ) every three weeks.…”
Section: Other Cytotoxic Agents Epothilonesmentioning
confidence: 99%
“…Tasidotin has also been shown to have unique effects on microtubules (3). At low concentrations (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) Amol/L), tasidotin seems to induce a prolonged lag phase in microtubule assembly, which is followed by the standard rate of microtubule assembly. At higher concentrations (>50 Amol/L), tasidotin inhibits the extent of microtubule assembly and induces a long lag time, which is not a feature of other antimicrotubule agents.…”
mentioning
confidence: 99%